Descriptive analysis and relationship between physical activity and academic performances in young students from central Spain - Samuel Manzano-Carrasco; Sebastián López-Serrano; Sara Suárez-Manzano; Alberto Ruiz-Ariza (INFAD, 2018)
Evidence suggests that the practice of physical activity (PA) is positively related to academic performance in adolescents. However, there is little information about whether the improvements affect in the same way in all subjects according to the weekly level of PA at a moderate-vigorous intensity (MVPA). The objective was to describe and see the relationship that exists between the weekly practice of MVPA with the academic performance of young students between 12 and 16 years old. A descriptive design was used. MVPA and the subjects’ marks were evaluated through a sociodemographic questionnaire. The results showed significance in the children where they perform more MVPA than the girls during the week. On the other hand, in both sexes, it was statistically significant to have better grades in physical education (PE) with the increase in weekly MVPA. No significant differences were found in the subjects of language, mathematics and english or french. Therefore, the practice of daily and weekly MVPA is a way to improve the marks in the subject of PE, apart from the benefits it has for health. Future studies are required to contrast this study with a higher sample or even measure some cognitive variables.